A new species of Letheobia (Serpentes: Typhlopidae) from central Kenya - Malonza, Patrick K.; Bauer, Aaron M.; Ngwava, Jacob M. (Zootaxa, 2016)
A new species of blind snake in the genus Letheobia (L. mbeerensis sp. nov.) is described from the Mbeere area on the extreme lower slopes of southeastern Mt. Kenya. It is an attenuate blind snake, superficially similar to Letheobia lumbriciformis but with 20 midbody scale rows and 670 middorsal scales. It has a total length of 280 mm with the proportionally longest tail in the genus (2.9% of total length), a broad rostral, eyes barely visible and in life it is pink in color. The new species is known from only a single specimen collected at Siakago, in Mbeere-Embu, which lies at an elevation of about 1200m. It is a burrowing species and like many other blind snakes it is likely to be nocturnal and rarely encountered on the soil surface. The new species is incorporated into a key to the scolecophidian snakes of Kenya.